2013
DOI: 10.1007/s11367-012-0542-4
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of light-emitting diode downlight luminaire—a case study

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…3. The results of the Tähkämö et al (2013) study were confirmed in a more recent comparative LCA for LED lighting products, which also considered an even shorter scenario of 1000 hours lifetime (compared to 15,000 and 40,000 hours lifetimes) (Casamayor et al 2017). Not only did the assumption of shorter lifetimes result in significantly higher impacts of both LED products considered, but it also resulted in the main environmental impacts coming from the manufacturing, rather than the use phase.…”
Section: Lca Approachsupporting
confidence: 60%
See 2 more Smart Citations
“…3. The results of the Tähkämö et al (2013) study were confirmed in a more recent comparative LCA for LED lighting products, which also considered an even shorter scenario of 1000 hours lifetime (compared to 15,000 and 40,000 hours lifetimes) (Casamayor et al 2017). Not only did the assumption of shorter lifetimes result in significantly higher impacts of both LED products considered, but it also resulted in the main environmental impacts coming from the manufacturing, rather than the use phase.…”
Section: Lca Approachsupporting
confidence: 60%
“…However, certain factors can influence the distributions, including lifetimes. Tähkämö et al (2013) also found that the shorter the LED lifetime, the larger the share of manufacturing in the total life cycle impacts (due to the need for manufacturing additional replacement lamps), as shown in Fig. 3.…”
Section: Lca Approachmentioning
confidence: 83%
See 1 more Smart Citation
“…(Parson, 2006). All the comparative studies indicate this condition (Michaud andBelley, 2008, DEFRA, 2009;Ramroth, 2008;OSRAM, 2009;Weltz, et al, 2011;Elijošiutė et al, 2012;DOE, 2012b,Tähkämö et al, 2013Hadi et al, 2013;Principi e Fioretti, 2014;Sangwanet al, 2014;Tahkamo et al, 2014;Bergesen et al, 2015;Tan et al, 2015;Yu et al, 2016). DOE (2012b) and OSRAM (2009) already indicate that LED lamps will be able to reduce more emissions when achieving its technological apex.…”
Section: Results Comparisons and Influencesmentioning
confidence: 97%
“…street light bulb VS household light bulb) and functional unit (as shown in Table 2). Thus, results can vary considerably, for example, 0.32 kg of CO2 equivalent (Principi and Fioretti, 2014) to 3,300 kg CO2 equivalent (Hadi et al, 2013) for LED LCAs, as can show similarities, 115.4 kg of CO2 equivalent (OSRAM, 2009) to 112 kg CO2 equivalent (Tähkämö et al, 2013). Other methodological definitions (e.g.…”
Section: Results Comparisons and Influencesmentioning
confidence: 99%